2009
DOI: 10.1242/dev.028902
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 controls cardiac neural crest cell migration during arch artery development by regulatingGbx2expression in the pharyngeal ectoderm

Abstract: Elucidating the gene regulatory networks that govern pharyngeal arch artery(PAA) development is an important goal, as such knowledge can help to identify new genes involved in cardiovascular disease. The transcription factor Tbx1 plays a vital role in PAA development and is a major contributor to cardiovascular disease associated with DiGeorge syndrome. In this report, we used various genetic approaches to reveal part of a signalling network by which Tbx1 controls PAA development in mice. We investigated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 80 publications
(129 reference statements)
11
161
4
1
Order By: Relevance
“…22 Of note, a pathogenic role for neural crest cells was also suspected for Lujan-Fryns Syndrome with the involvement of MED12, another member of the Mediator complex. 23 In addition, MED13L and other subunits of the Mediator complex were recently shown to have a role in Rb/E2F-induced growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Of note, a pathogenic role for neural crest cells was also suspected for Lujan-Fryns Syndrome with the involvement of MED12, another member of the Mediator complex. 23 In addition, MED13L and other subunits of the Mediator complex were recently shown to have a role in Rb/E2F-induced growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The third patient is a girl born 5 days preterm with a history of transient but marked fetal hydrops during pregnancy (weeks [16][17][18][19][20][21][22][23][24][25]. Her birth weight was 2200 g (o3rd centile) and the length was 47 cm (3rd centile).…”
Section: Patientmentioning
confidence: 99%
“…To identify putative shared targets, we followed a candidate gene approach. We considered three Tbx1 target genes that are known to interact with Tbx1 during fourth PAA development: Gbx2, Smad7, and Wnt5a (17,24,25). We first tested the expression of these genes in WT, Tbx1 +/− , Trp53 +/− , and Tbx1 +/− ; Trp53 +/− E8.5 embryos using quantitative reverse transcription PCR.…”
Section: Trp53 Mutation Modifies the Hypomorphic But Not The Null Tbx1mentioning
confidence: 99%
“…Surprisingly, we found that Tbx1 and p53 cooccupy chromatin segments, suggesting that they have shared targets. Indeed, we found that Gbx2, a gene required during cardiovascular development and known to genetically interact with Tbx1 (16,17), is targeted by both transcription factors. Specifically, it is down-regulated by Tbx1 deletion, but its expression is reestablished to wild-type levels in the presence of Trp53 deletion.…”
mentioning
confidence: 94%
“…Tbx1, a putative T-box transcription factor, is expressed in the pharyngeal endoderm, ectoderm, and core mesoderm [4][5][6]. Celltype-specific inactivation in mice and analysis of Tbx1 downstream targets indicate that it plays multiple roles in endoderm, mesoderm, and ectoderm cells during pharyngeal development [7][8][9]. In humans, Tbx1 is involved in the DiGeorge syndrome, which is associated with cardiac malformations as well as other developmental anomalies of organs and structures derived from the pharyngeal apparatus [10].…”
Section: Introductionmentioning
confidence: 99%